2014
DOI: 10.1007/s10863-014-9571-y
|View full text |Cite
|
Sign up to set email alerts
|

Idebenone and neuroprotection: antioxidant, pro-oxidant, or electron carrier?

Abstract: Ubiquinone, commonly called coenzyme Q10 (CoQ), is a lipophilic electron carrier and endogenous antioxidant found in all cellular membranes. In the mitochondrial inner membrane it transfers electrons to complex III of the electron transport chain. The short chain CoQ analogue idebenone is in clinical trials for a number of diseases that exhibit a mitochondrial etiology. Nevertheless, evidence that idebenone ameliorates neurological symptoms in human disease is inconsistent. Although championed as an antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 82 publications
1
81
0
2
Order By: Relevance
“…Due to the indispensable function in the processes of oxidative phosphorylation, Coenzyme Q-10 (CoQ-10) and its derivatives are the most prominent members in the family of Q/HQ [4][5][6][7]. Although the number of studies related to the chemical and redox features of CoQ family members has increased tremendously in the last three decades [8][9][10][11][12][13][14][15][16][17][18], many key features are still not well understood. In our last two publications we have shown that Coenzyme Q-1 (CoQ-1) and CoQ-10 undergo structural changes in strong alkaline environment or in the presence of Cytochrome P450 enzymes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the indispensable function in the processes of oxidative phosphorylation, Coenzyme Q-10 (CoQ-10) and its derivatives are the most prominent members in the family of Q/HQ [4][5][6][7]. Although the number of studies related to the chemical and redox features of CoQ family members has increased tremendously in the last three decades [8][9][10][11][12][13][14][15][16][17][18], many key features are still not well understood. In our last two publications we have shown that Coenzyme Q-1 (CoQ-1) and CoQ-10 undergo structural changes in strong alkaline environment or in the presence of Cytochrome P450 enzymes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Side effects are more relevant at time of loss of ambulation (i.e., alteration of bone metabolism and risk of spontaneous fractures) [15]. This gap has been fixed by the introduction of a different molecule: idebenone, a short-chain benzoquinone characterized by potent antioxidant activity and with the ability to stimulate mitochondrial electron flux and cellular energy production [16,17]. It has been shown in multicenter clinical trials that idebenone is able to slow the decline of pulmonary function of DMD patients, with a consequent reduced risk of bronchopulmonary complications and a reduced need for systemic antibiotics [6,7,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Idebenone, is a synthetic analog of coenzyme Q10, an endogenous antioxidant found in all cellular membranes, and a constituent of the adenosine triphosphate-producing electron transport chain of mitochondria [84]. In addition to antioxidant properties, idebenone has been shown to exert anti-inflammatory effects in vitro [85].…”
Section: Idebenonementioning
confidence: 99%